Antibiotic susceptibility of environmental isolates Burkholderia species - Flowrence Vianney, Sylvester (Universiti Malaysia Sarawak, 2017)
Antibiotics are antibacterial drugs that have been used for more than a 100 years to treat patients infected by bacterial infections where the use of antibiotics has successfully reduced illnesses and deaths. However, excessive and misuse of antibiotics has caused many bacteria to develop resistance against antibiotics. The Burkholderia species comprising of more than 70 members co-exist in the same ecological niche and this gives rise to interspecies competitions. It raises the question of whether their reaction to antibiotics is similar to that of Burkholderia pseudomallei, a member of the Burkholderia species which is pathogenic to human and animals. In this project, Burkholderia species, Ralstonia species and Achromobacter xylosidians were tested for their antibiotics susceptibility against gentamicin, ceftazidime, sulphamethoxazole/trimethoprim and azithromycin by using the disk diffusion test. The antibiogram profiles of the majority of Burkholderia spp. isolates tested in the study were consistent with that B. pseudomallei. This suggests that there may be similarities in the drug susceptibility of the mechanism of Burkholderia spp. and B. pseudomallei which is more well described due to its clinical importance.